Precise processing of pure undiluted PEGDA via inkjet printing for drug release systems - Sannan Ahmed; Eickner Thomas; Teske Michael; Mau Robert; Grabow Niels; Seitz Hermann (Current Directions in Biomedical Engineering)
Poly(ethylene glycol) diacrylate (PEGDA) is a common polymer in the field of biomedical engineering and can be used for the production of drug delivery systems (DDS). The main advantages of PEGDA are biocompatibility and the ability to alter the physical and chemical properties, thereby ensuring individualized drug release behaviour. The processing of PEGDA via inkjet printing is relevant for the production of DDS. This can be challenging due to the high viscosity of pure PEGDA. In this work, PEGDA, with a molecular weight of 250 g/mol (PEGDA250), was inkjet printed using a Nanoplotter 2.1 with a piezoelectric heatable NanoTip HV-J-H printhead (GeSiM mbH, Radeberg, Germany) at different voltages and temperatures. Droplet generation was analysed in terms of droplet volume and angle deviations. PEGDA250 can be inkjet printed reproducibly in a voltage range of 60 V - 80 V at room temperature (20 °C) or heated up to 38 °C. The average volume of heated (38 °C) PEGDA250 droplets was approximately 110 pl - 150 pl higher than the droplet volume of PEGDA250 in the unheated state. The average angle deviations of main and satellite droplets were mostly < 3°. Increasing voltage or excessive heating of more than 38 °C caused greater instabilities in the droplet generation as well as larger satellite droplets which can affect the accuracy negatively. The studies have shown that PEGDA250 can be processed via inkjet printing and thus can be used as a drug carrier for DDS without the need for mixing with a solvent.